Implementation of the Development Plan Policy Regional Long-Term Development Plan (RPJPD) Sumedang Regency 2005-2025 - Ellan Rohelan Nagari; Petrus Polyando; Eva Eviany (INFOKUM, 2025)
This research is motivated by the fact that the implementation of the 2005–2025 Sumedang Regency Long-Term Development Plan (RPJPD) policy as a strategic document for long-term development has not been achieved. The main problems in this research are: (1) how is the implementation of the 2005–2025 Sumedang Regency RPJPD policy, and (2) what are the obstacles faced in its implementation. This research aims to comprehensively describe the process of implementing the RPJPD policy and identify factors inhibiting its implementation for two decades. The method used in this research is a qualitative method (quasi-qualitative) with a case study approach. Data collection techniques were carried out through semi-structured interviews with various key informants, consisting of elements of the Regional Head/Deputy Regional Head, DPRD, bureaucracy, community leaders, and supporting documentation. Data were analyzed thematically using the Miles and Huberman interactive model. The results of the study indicate that the implementation of the Sumedang Regency RPJPD has not been fully implemented substantially. This policy tends to be a formality document without adequate supervision and evaluation. The major obstacles are the large influence of regional heads, limited human resource capacity, minimal cross-agency coordination, and the absence of an evaluation system and integration of planning documents. The conclusion of the study shows that the success of the implementation of the RPJPD is greatly influenced by political commitment, institutional systems, and sustainability between periods. Therefore, the main suggestion is the need for an integrated regional planning system reform, strengthening the role of Bappeda, determining a special RPJPD supervisor, and periodic evaluation based on indicators.